Discharge Considerations for Adult Asthmatic Patients Treated in Emergency Departments - Anton F Grunfeld; J Mark FitzGerald (Canadian Respiratory Journal)
OBJECTIVE: To review the medical literature on outcome of treatment of acute asthma in the emergency department and issue recommendations regarding patient admission or discharge.